2020
DOI: 10.1126/science.aax4040
|View full text |Cite
|
Sign up to set email alerts
|

PIRs mediate innate myeloid cell memory to nonself MHC molecules

Abstract: Immunological memory specific to previously encountered antigens is a cardinal feature of adaptive lymphoid cells. However, it is unknown whether innate myeloid cells retain memory of prior antigenic stimulation and respond to it more vigorously on subsequent encounters. In this work, we show that murine monocytes and macrophages acquire memory specific to major histocompatibility complex I (MHC-I) antigens, and we identify A-type paired immunoglobulin-like receptors (PIR-As) as the MHC-I receptors necessary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(109 citation statements)
references
References 28 publications
(25 reference statements)
1
85
0
Order By: Relevance
“…As to the mechanisms by which monocytes acquire allospecific memory, the PIR molecules were preferentially expressed on Ly6Chi monocytes, which significantly expanded after allogeneic antigen exposure. Specific memory independent of lymphoid cells can be transferred to an unimmunized recipient by transferring sorted Ly6Chi monocytes expanded from an immunized recipient, suggesting that clonal expansion of monocytes that express the particular PIR-A molecule that recognizes the particular MHC-I molecule in the immunogen underlies memory (51). This resembles the mechanism established in the case of allospecific NK cell memory (34).…”
Section: Allospecific Memory In Innate Immune Cells: Recognition Of Mmentioning
confidence: 88%
See 1 more Smart Citation
“…As to the mechanisms by which monocytes acquire allospecific memory, the PIR molecules were preferentially expressed on Ly6Chi monocytes, which significantly expanded after allogeneic antigen exposure. Specific memory independent of lymphoid cells can be transferred to an unimmunized recipient by transferring sorted Ly6Chi monocytes expanded from an immunized recipient, suggesting that clonal expansion of monocytes that express the particular PIR-A molecule that recognizes the particular MHC-I molecule in the immunogen underlies memory (51). This resembles the mechanism established in the case of allospecific NK cell memory (34).…”
Section: Allospecific Memory In Innate Immune Cells: Recognition Of Mmentioning
confidence: 88%
“…In the third set of experiments (51,61), innate allorecognition and memory molecular pathways were interrupted. We observed that mouse renal allografts transplanted to recipients that lack either CD47 or PIR-A develop significantly less manifestations of chronic rejection.…”
Section: Role Of Innate Allorecognition In Rejectionmentioning
confidence: 99%
“…More recently, the Lakkis laboratory also demonstrated that polymorphisms in the SIRPa gene were required to induce monocyte memory is against non-self MHC molecules. In this study, it was demonstrated that deleting the PIR-A in the recipient or blocking the paired immunoglobulin-like receptor-A (PIR-A) binding to donor MHC-I with a PIR-A3/Fc inhibits alloantigen specific memory of myeloid cells and promotes indefinite allograft survival in a murine kidney and heart transplant model (142). Overall, these studies provide compelling evidence demonstrating that monocytes initiate the immune response, determine the critical role of SIRPa polymorphic differences in the activation of graft reactive macrophages and that the immunological memory to innate myeloid cells can be potentially targeted to promote the induction of transplantation tolerance.…”
Section: Macrophages and Rejectionmentioning
confidence: 99%
“…Adaptive immunity focusing on T cell biology has dominated studies of transplant rejection in the past several decades. However, innate immunity has recently become recognized as an important player in transplantation ( 1 4 ), demonstrating previously unidentified roles in promoting ischemic reperfusion injuries ( 5 ), priming adaptive immune responses ( 1 , 6 ), or perpetuating chronic rejection ( 7 ). Among innate immune cells, tissue macrophages have been shown to influence organ homeostasis and defense ( 8 ).…”
Section: Introductionmentioning
confidence: 99%